A dual cone‐beam CT system for image guided radiotherapy: Initial performance characterization. Issue 2 (31st January 2013) - Li, Hao; Giles, William; Bowsher, James; Yin, Fang‐Fang
Abstract : Purpose: : The purpose of this study is to evaluate the performance of a recently developed benchtop dual cone‐beam computed tomography (CBCT) system with two orthogonally placed tube/detector sets. Methods: : The benchtop dual CBCT system consists of two orthogonally placed 40 × 30 cm flat‐panel detectors and two conventional x‐ray tubes with two individual high‐voltage generators sharing the same rotational axis. The x‐ray source to detector distance is 150 cm and x‐ray source to rotational axis distance is 100 cm for both subsystems. The objects are scanned through 200° of rotation. The dual CBCT system utilized 110° of projection data from one detector and 90° from the other while the two individual single CBCTs utilized 200° data from each detector. The system performance was characterized in terms of uniformity, contrast, spatial resolution, noise power spectrum, and CT number linearity. The uniformities, within the axial slice and along the longitudinal direction, and noise power spectrum were assessed by scanning a water bucket; the contrast and CT number linearity were measured using the Catphan phantom; and the spatial resolution was evaluated using a tungsten wire phantom. A skull phantom and a ham were also scanned to provide qualitative evaluation of high‐ and low‐contrast resolution. Each measurement was compared between dual and single CBCT systems. Results: : Compared to single CBCT, the dual CBCT presented: (1) a decrease in uniformity by 1.9% in axial view and 1.1% in the longitudinal view, as averaged for four energies (80, 100, 125, and 150 kVp); (2) comparable or slightly better contrast (0∼25 HU) for low‐contrast objects and comparable contrast for high‐contrast objects; (3) comparable spatial resolution; (4) comparable CT number linearity with R 2 ≥ 0.99 for all four tested energies; (5) lower noise power spectrum in magnitude. Dual CBCT images of the skull phantom and the ham demonstrated both high‐contrast resolution and good soft‐tissue contrast. Conclusions: : The performance of a benchtop dual CBCT imaging system has been characterized and is comparable to that of a single CBCT.